2020
DOI: 10.12681/bgsg.25359
|View full text |Cite
|
Sign up to set email alerts
|

First Results on the Mw=6.9 Samos Earthquake of 30 October 2020

Abstract: On 30 October 2020 11:51 UTC, a Mw=6.9 earthquake struck the offshore region north of Samos Island, Greece, in the Gulf of Ephesos/Kuşadasi, causing two fatalities and 19 minor injuries at Samos Island, as well as 115 casualties and over 1,030 injuries in Western Turkey. Preliminary results indicate that the mainshock occurred on a north-dipping normal fault, with a focal mechanism of 270º/50º/-81º. The selection of the fault plane is supported by evidence of uplift at western Samos and over 10 cm of subsidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
5
32
0
Order By: Relevance
“…Such a focal mechanism is consistent with the tectonic setting of the area [4][5][6][7][8][9][10]. The largest aftershock occurred a few hours after the main event (30 October 2020, 15:14:57 UTC) and its magnitude was calculated as Mw = 5.0 [1]. From the records of an SMG1 accelerometer installed in Vathy town, northeastern Samos, it was concluded that the peak ground acceleration (PGA) in the two horizontal components was 0.16 g and 0.23 g, respectively, while in the vertical component a PGA of 0.13 g was measured [11].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Such a focal mechanism is consistent with the tectonic setting of the area [4][5][6][7][8][9][10]. The largest aftershock occurred a few hours after the main event (30 October 2020, 15:14:57 UTC) and its magnitude was calculated as Mw = 5.0 [1]. From the records of an SMG1 accelerometer installed in Vathy town, northeastern Samos, it was concluded that the peak ground acceleration (PGA) in the two horizontal components was 0.16 g and 0.23 g, respectively, while in the vertical component a PGA of 0.13 g was measured [11].…”
Section: Introductionsupporting
confidence: 62%
“…On 30 October 2020 (11:51:26 UTC), a very strong earthquake measuring moment magnitude Mw = 7.0 ruptured offshore to the north of Samos Island in the eastern Aegean Sea (Greece) (Figure 1) [1]. Fault plane solutions showed the activation of an E-W striking normal fault, which is likely dipping to the north [2,3] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the rapid response, just a few hours after the event, thanks to the availability of synthetic aperture radar (SAR) data acquired from the Sentinel-1 mission of the European Union's Copernicus Programme, on the same day as the earthquake and less than 12 h apart, several scientific groups communicated their Differential Interferometric SAR (DInSAR) results on social media (Twitter, LinkedIn, Facebook, etc. ) or by preliminary reports (Chatzipetros et al 2020;Ganas et al 2020;Lekkas et al 2020;Papadimitriou et al 2020;Segou 2020). This information was available in addition to solutions obtained from regional GNSS networks covering the affected area (Ganas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It might be synchronous to the onshore Upper Miocene volcanic formations of Samos, observed along the Mytilini and Karlovassi basins (see Figure 2). [10] generally show E-W normal faulting (Figure 6a). The main shock (Magnitude 7.0) and most of the aftershocks (Magnitudes 5.2-3.9) occur in the central and eastern part of Samos Basin, forming a 20 km long seismic belt, which is smaller than expected for this magnitude (following the empirical relationships [45]).…”
Section: Discussionmentioning
confidence: 99%
“…The mainshock occurred on 30 October with magnitude 7.0 [10,11], and its focal mechanism indicated an E-W trending normal fault dipping to the north. Its epicenter is located about 8-10 km north of Samos Island to the north of Karlovassi, situated at the basinal area of the Samos Basin [12].…”
Section: Introductionmentioning
confidence: 99%